Enhanced moisture permeability and heat dissipation effect of solvent-free boron nitride fluids based polylactic acid fibrous membranes. (January 2022) - Shen, Hui; Wang, Junfeng; Li, Yushan; Zheng, Long; Xiong, Siwei; Chen, Zhenming; Yin, Xianze
Abstract: Exceptional moisture permeability and heat dissipation performance are vital for wearable polymer fabrics. In this study, solvent-free boron nitride fluids (BNfs) with liquid-like behavior were prepared via an ion exchange reaction. The BNfs were then incorporated into polylactic acid (PLA) fibrous membranes to endow the membranes with multifunctionality. The results showed that the surface wetting behavior of the membranes containing 15 wt% and 20 wt% BNfs changed the hydrophobicity of pure PLA to superhydrophilicity, showing excellent moisture permeability. PLA/BNfs fibrous membranes with 20 wt% loading had 2.9-fold increased thermal conductivity when compared with pure PLA, leading to an enhanced heat dissipation effect. Additionally, the PLA/BNfs fibrous membrane had better mechanical properties than the pure PLA. The resultant multifunctional PLA/BNfs fibrous membranes have great application prospects in flexible wearable fabrics. Graphical abstract: Image 1 Highlights: BNfs were designed and embedded into PLA fibrous membranes via electrospinning. The PLA/BNfs fibrous membranes show improved mechanical properties and toughness. Moisture permeability and heat dissipation effect of the membranes are enhanced. The resultant multifunctional membranes can be used as flexible wearable fabrics.